Videos in learning in higher education: assessing perceptions and attitudes of students at the University of Ghana - Boateng, R.; Boateng, S.L.; Awuah, R.B; Ansong, E.; Anderson, A.B. (SPRINGER, 2016)
Video is one of the most diversified and distinct virtual learning mediums that capture and present information and offer a sensory learning environment, which enables learners to understand more and retain information better. This study sought to assess the perceptions and attitudes of students at the University of Ghana towards the use of videos as a medium for teaching and learning. Qualitative data was collected using semi structured interviews. Participation was entirely voluntary and was conditional, based on students’ verbal consent. A convenience sample of 20 students responded to a request to participate, and data was analyzed using content analysis. Students perceived videos in general as being of some benefit to their learning activities. Overall, comments on videos as a medium of teaching and learning were positive. However, students had negative perceptions about the nature of the videos they watched. Almost all the participants indicated that they had issues with the content and the format of all the videos they watched. But, majority of the participants perceived that the videos they watched enhanced their learning outcomes and improved their learning approach. Therefore, learning outcomes of students and instructors should be dependent on the manner in which videos are used, as part of the overall academic process. This study is one of the first articles to explore in detail, students’ perceptions and attitudes towards video based teaching in Ghana, and provides interesting insights with regard to the concept and its application in tertiary institutions.
Keywords: Video supported learning; E-learning; Higher learning institutions; Developing countries